2009
DOI: 10.1186/alzrt7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent treatment with cholinesterase inhibitors and/or memantine slows clinical progression of Alzheimer disease

Abstract: IntroductionThere are no empiric data to support guidelines for duration of therapy with antidementia drugs. This study examined whether persistent use of antidementia drugs slows clinical progression of Alzheimer disease (AD) assessed by repeated measures on serial tests of cognition and function.MethodsSix hundred forty-one probable AD patients were followed prospectively at an academic center over 20 years. Cumulative drug exposure was expressed as a persistency index (PI) reflecting total years of drug use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(116 citation statements)
references
References 40 publications
5
107
1
3
Order By: Relevance
“…In addition, some long-term observations suggest less decline in patients treated with AChE-Is or combination therapy of AChE-Is with memantine compared to P.S. Aisen et al patients not receiving therapy with these agents (Lopez et al 2009;Rountree et al 2009). Other clinical and imaging studies, however, suggest no disease-modifying benefit from treatment with AChE-Is (Jack et al 2008;Schneider and Sano 2009).…”
Section: Symptomatic and Other Treatments For Alzheimer Diseasementioning
confidence: 99%
“…In addition, some long-term observations suggest less decline in patients treated with AChE-Is or combination therapy of AChE-Is with memantine compared to P.S. Aisen et al patients not receiving therapy with these agents (Lopez et al 2009;Rountree et al 2009). Other clinical and imaging studies, however, suggest no disease-modifying benefit from treatment with AChE-Is (Jack et al 2008;Schneider and Sano 2009).…”
Section: Symptomatic and Other Treatments For Alzheimer Diseasementioning
confidence: 99%
“…It also finds that combined treatment is superior to monotherapy. A previous large scale investigation [8] found that patients on continuous anti-dementia treatment lived three years longer, on average, than those who had no treatment or interrupted medication. Add to this a finding from residential care settings [9] documenting better function in patients taking anti-dementia medication, including a reduced need for antipsychotic medications that carry an FDA "black-box" warning.…”
Section: We Concur and Here Is Whymentioning
confidence: 99%
“…These were studies of patients whose treatments had been extended after completing the three-and six-month pharmaceutical company-sponsored registration trials (Doody et al, 2001;Geldmacher et al, 2003;Pirttilä et al, 2004;Raskind et al, 2004;Small et al, 2005;Burns et al, 2007;Feldman et al, 2009;Kavanagh et al, in press), and of patients tracked in academic and research clinics (GilletteGuyonnet et al, 2006;Atri et al, 2008;Lopez et al, 2009;Rountree et al, 2009). In these studies, patients continuing medications were compared to patients who had never been treated, used the drugs only briefly, or had dropped out of the randomized trials for one reason or another; some of the studies also used "projected" data from placebo patients, or historical data.…”
Section: Long-term Studies Of Cholinesterase Inhibitorsmentioning
confidence: 99%